Peningkatan Hasil Belajar Matematika Siswa Menggunakan Model Pembelajaran Berbasis Masalah Berbantuan Multimedia Interaktif - Tandri Patih; Halistin Halistin; Muhammad Syarwa Sangila; Imaludin Agus; Dedyerianto Dedyerianto; Amanda La Hadi; Nur Aini; La Ode Sardin; Samrin Samrin (Institut Agama Islam Negeri Kendari, 2020)
This article reports the result of semi-experimental study which aims to determine and assess the improvement of students’ mathematics learning outcomes after they are exposed to interactive multimedia-assisted problem-based learning model. The sample is 7th grade students at one of junior high school in Kendari. They were selected using cluster random sampling technique. Based on the result of data analysis using descriptive and inferential statistics, the interactive multimedia assisted-problem based learning can improve the students’ mathematics learning outcomes. The result of the study revealed the increase of the average after being taught with interactive multimedia assisted-problem based learning models with 21.2 units and the significance value of 0.00. Interactive multimedia-assisted-problem based learning can be an alternative for mathematical activeness and abilities, which have an impact on improving student mathematics learning outcomes.